ON THE SULFATE PARTICLES IN THE SUBMICRON SIZE RANGE COLLECTED AT MIZUHO STATION AND IN EAST QUEEN MAUD LAND, ANTARCTICA : PRELIMINARY RESULTS - ヤマト, マサヒコ; イワサカ, ヤスノブ; オノ, アキラ; ヨシダ, ミノル; YAMATO, Masahiko; IWASAKA, Yasunobu; ONO, Akira; YOSHIDA, Minoru (National Institute of Polar Research, 1987)
P(論文) Aerosol particles were sampled at Mizuho Station (70°42′S, 44°20′E) and in East Queen Maud Land (73°06′-74°50′S, 39°45′-34°56′E), Antarctica from April to November in 1984. The vapor-deposited BaCl_2 thin film method was used to identify sulfate-containing particles. Morphological identification of the individual particles was also made in order to determine their actual molecular state. It was confirmed from the morphology of particles that particles containing sulfuric acid were predominant in East Queen Maud Land in summer, whereas ammonium sulfate particles were predominant in winter at Mizuho Station. These results are similar to the results at Syowa Station (T. ITO, Pap. Meteorol. Geophys., 34,151,1983). An interesting finding is that sulfuric acid particles existed as a minor component at Mizuho Station even in winter when photochemical production of sulfuric acid particles was not dominant. departmental bulletin paper